Expansion of sesquiterpene biosynthetic gene clusters in pepper confers nonhost resistance to the Irish potato famine pathogen. Issue 3 (20th June 2017) - Lee, Hyun‐Ah; Kim, Sejun; Kim, Seungill; Choi, Doil
Summary: Chemical barriers contribute to nonhost resistance, which is defined as the resistance of an entire plant species to nonadapted pathogen species. However, the molecular basis of metabolic defense in nonhost resistance remains elusive. Here, we report genetic evidence for the essential role of phytoalexin capsidiol in nonhost resistance of pepper ( Capsicum spp.) to potato late blight Phytophthora infestans using transcriptome and genome analyses. Two different genes for capsidiol biosynthesis, 5‐ epi ‐aristolochene synthase ( EAS ) and 5‐ epi ‐aristolochene‐1, 3‐dihydroxylase ( EAH ), belong to multigene families. However, only a subset of EAS/EAH gene family members were highly induced upon P. infestans infection, which was associated with parallel accumulation of capsidiol in P. infestans ‐infected pepper. Silencing of EAS homologs in pepper resulted in a significant decrease in capsidiol accumulation and allowed the growth of nonadapted P. infestans that is highly sensitive to capsidiol. Phylogenetic and genomic analyses of EAS / EAH multigene families revealed that the emergence of pathogen‐inducible EAS / EAH genes in Capsicum ‐specific genomic regions rendered pepper a nonhost of P. infestans . This study provides insights into evolutionary aspects of nonhost resistance based on the combination of a species‐specific phytoalexin and sensitivity of nonadapted pathogens.